PEMANFAATAN TEKNOLOGI DIGITAL DALAM KEGIATAN PEMBELAJARAN - Hidayat, Nandang; Khotimah, Husnul (JPPGuseda | Jurnal Pendidikan & Pengajaran Guru Sekolah Dasar, 2019)
This research study aims to systematically review a variety of digital technologies that are currently developing so rapidly to be optimally utilized according to the ability of teachers and technological devices owned by schools, teachers, and students. This study uses the method of review of integrative literature. This method combines various empirical and research-based articles, books, and other published literature on digital competencies and their use in 21st century education. The literature research concludes: 1) Digital literacy is the awareness, attitude, and ability of individuals to properly use tools and digital facilities to identify, access, manage, integrate, evaluate, analyze, and synthesize digital resources, build new knowledge, make media expressions, and communicate with others, in the context of certain life situations, to enable constructive social action; 2) Digital competency is a set of knowledge, skills, attitudes needed when using ICT and digital media for various needs; 3) Digital technology that can be used by schools / teachers in the learning process including interactive whiteboards (IWB), software applications, Web 2.0, and social media; and 4) Utilization of digital technology in learning can increase students' interest and motivation in learning, the quality of learning processes, and learning outcomes, but need to pay attention to various aspects of the ability of human resources, security, and health of teachers and students.